Giant Idiopathic Pulmonary Artery Aneurysm: An Interesting Incidental Finding - Afsoon Fazlinejad; Mohammad Vojdanparast; Reza Jafarzadeh Esfehani; Sahar Sadat Moosavi; Parisa Jalali (Case Reports in Vascular Medicine)
Idiopathic pulmonary artery aneurysm is a rare condition. This type of aneurysm can be presented with noncardiac symptoms or even asymptomatic. We report a 73-year-old man with a gigantic idiopathic pulmonary artery aneurysm which was referred to our unit for his kidney problems. During his workup we incidentally found the aneurysm by an abnormal chest-X ray and auscultation. Our further evaluations revealed a 9.8 cm aneurysm in transthoracic echocardiography.